PERTUNJUKAN OPERA AGNUS PERDITUS KARYA MATHEUS WASI BANTOLO - Estherlita Priskanike Yudiaernanda; Supriyanto Supriyanto (Institut Seni Indonesia Surakarta, 2021)
Agnus Perditus is a dance genre opera, Agnus Perditus is taken from Latin means lost sheep. The work of Agnus Perditus was directed by Matheus Wasi Bantolo for a joint Christmas event between the Indonesian Institute of the Arts Surakarta and Sebelas Maret University which was held at Teater Besar of the Indonesian Art Institute, Surakarta. In 2016 the combined Christmas was directed by Matheus Wasi Bantolo. The theoretical basis in this study uses the concept of working on Rahayu Supanggah which examines the process of working on an art, as well as the theory of form approach from Suzanne K. Langer in her book entitled